Relaxation and physicomechanical characteristics of polyethylenes with different molecular weights - R. A. Alekhina; V. A. Lomovskoy; I. D. Simonov-Emel’yanov; S. A. Shatokhina (Тонкие химические технологии, 2019)
Objectives. Determination of the influence of molecular weight on the modulus of elasticity, yield, strength, and retardation processes in polyethylene.Methods. We used vane samples (thickness: 4 mm; length: 100 mm; width.: 10 mm) made by injection molding at p = 60 MPa, T = 210 °C, τ = 15 s from the following polyethylenes: HDPE 27773 (Stavrolen, Lukoil, Russia); BorSafe HE3490-IM (Borealis, Austria; black); CRP 100 Hostalen (Basell Polyolefins, Netherlands; black); Stavrolen PE4PP-25B (Stavrolen, Lukoil, Russia; black). The samples were in accordance with the defined standards for the AL 7000 LA-5 tensile testing machine. The study of relaxation characteristics was carried out in two modes: relaxation and retardation.Results. We obtained stress-strain diagrams at various temperatures under isothermal conditions (T = const) and determined the influence of polyethylene molecular weights on the modulus of elasticity, yield, and strength of polyethylenes. We have shown that under isothermal conditions, when the stress equals the yield strength, the removal of the external action results in a two-stage response. The first stage is the stress relaxation. The second stage characterizes the elastic features of the studied materials under the external action ε = const.Conclusions. We have established that temperature increase affects the physicomechanical characteristics of polyethylenes differently, depending on their molecular weights. The experiments have shown that when the stress exceeds the yield strength, at constant deformation, there is a complex response of the polyethylenes to external action. This response is characterized by two stress stages throughout the course of time. The first stage is characterized by asymptotic decrease in stress down to a constant value; the second stage is characterized by constant stress throughout the course of time. We have determined relaxation times for the relaxation stage (stage I) and calculated activation energy. We have also established that the activation energy depends on molecular weights of the polyethylenes. It has been shown that an increase in polyethylene molecular weight leads to a decrease in relaxation time and activation energy.